A Portrait of the Visual Arts Meeting the Challenges of a New Era - McCarthy, Kevin F. (RAND Corporation, 2005)
The third in a series that examines the state of the arts in America, this analysis shows, in addition to lines around the block for special exhibits, well-paid superstar artists, flourishing university visual arts programs, and a global expansion of collectors, developments in the visual arts also tell a story of rapid, even seismic change, systemic imbalances, and dislocation.